Análisis de la evidencia observacional de energía oscura (2021)
Dark energy is the most important standing problem in modern cosmology. This form of energy is responsible for the accelerated expansion of space-time in our universe. During the last two decades the observational evidence of its existence has been consolidated and the determination of its density and its equation-of-state parameter have been achieved to very high precision. However, recently, two problems have emerged: the so-called Hubble Tension and the controversy about the use of Type Ia supernovae (SN Ia) as standard candles. These problems have aroused questions about the existence of dark energy and of the validity of the Lambda CDM model. The outcome of this debate could even produce a change of paradigms that would transform our understanding of the cosmos. In this monograph, a detailed analysis of the observational evidence of dark energy, the SN 1a controversy and the Hubble tension are presented, and their implications for modern cosmology are explored.